Effect of Dietary Supplementation of Moringa oleifera Leaf Meal on Production and Reproduction in Rhode Island Red Chicken - D.G. Vaghamashi; D. D. Garg; G. P. Sabapara; K. B. Vala; J. A. Chavda; D. N. Borkhatariya; V. V. Gamit; H. P. Vijyeta (Indian Journal of Animal Nutrition, 2026)
A study was carried out to determine the effect Moringa oleifera leaf meal (MOLM) on production performance, semen quality, fertility, hatchability and chick quality of Rhode Island Red (RIR) chickens. One hundred and eighty, 24-week-old Rhode Island Red layer birds were randomly allotted to four dietary treatments having replicates with 15 birds in each. The treatments were T1 (Control: Basal diet); T2: 1% MOLM in basal diet; T3: 3% MOLM in basal diet; T4: 5% MOLM in basal diet. To study reproductive performance, 24 cocks at the age of 24th weeks were kept separately and equally divided into four groups and were provided same dietary treatments as provided to hens. The results revealed that average daily feed intake per bird (g/day) was lower (P